2014
DOI: 10.1016/j.jacc.2014.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Replacement in Bicuspid Aortic Valve Disease

Abstract: TAV-in-BAV is feasible with encouraging short- and intermediate-term clinical outcomes. Importantly, a high incidence of post-implantation AR is observed, which appears to be mitigated by MSCT-based TAV sizing. Given the suboptimal echocardiographic results, further study is required to evaluate long-term efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
127
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(134 citation statements)
references
References 42 publications
6
127
0
1
Order By: Relevance
“…A multicenter registry of 108 patients reported 30‐day and 1‐year mortality rates of 8.3% and 16.9%, respectively 35. An analysis of 139 low‐ and intermediate‐risk patients (mean STS score 4.9±3.4%) in 12 European centers corroborated these findings with 1‐year mortality of 17.5% 36. Another multicenter observational study comparing TAVR in patients with bicuspid versus tricuspid aortic valves did not demonstrate any difference in 30‐day mortality 40.…”
Section: Do Clinical Trials Of Tavr In Low‐risk Patients Herald the Ementioning
confidence: 84%
See 3 more Smart Citations
“…A multicenter registry of 108 patients reported 30‐day and 1‐year mortality rates of 8.3% and 16.9%, respectively 35. An analysis of 139 low‐ and intermediate‐risk patients (mean STS score 4.9±3.4%) in 12 European centers corroborated these findings with 1‐year mortality of 17.5% 36. Another multicenter observational study comparing TAVR in patients with bicuspid versus tricuspid aortic valves did not demonstrate any difference in 30‐day mortality 40.…”
Section: Do Clinical Trials Of Tavr In Low‐risk Patients Herald the Ementioning
confidence: 84%
“…First, the rate of moderate or severe PVL could be higher. Observational studies have reported PVL rates in bicuspid valves to range from 9.6% to 28.4% 35, 36. However, careful valve sizing using cardiac computed tomography angiography can reduce the incidence of PVL substantially 36.…”
Section: Do Clinical Trials Of Tavr In Low‐risk Patients Herald the Ementioning
confidence: 99%
See 2 more Smart Citations
“…BAV disease was an exclusion criterion in fundamental clinical trials to test the safety and efficacy of TAVI, largely because of the unique morphological features and associated aortic pathology of this condition 2, 3. Limited data exist for outcomes from TAVI in BAV and, despite promising single‐center series,4, 5 a recently published multi‐center series raised concerns about the excess of paravalvular regurgitation 6…”
Section: Introductionmentioning
confidence: 99%